O Grupo de Trabalho de Educação em Sexualidade da rede municipal de ensino do Recife: limites e avanços da sua atuação a partir das perspectivas religiosas de docentes - Melo, Valdir Eneias de (2018)
The main objective of this research was to analyze the limits and advances of the Working Group on Sexuality Education - GTES, of the Municipal Education Network, Recife, about the issues of sexual and gender diversity, seeking to detect the influence of the religious perspectives of teachers in the implementation of actions from continuing training. The theme of sexuality education is part of the Education Policy of the Recife Municipal Network, which guides pedagogical approaches to issues involving sexuality and gender from Early Childhood Education to Youth, Adult and Elderly Education (EJAI). In order to guide the teachers of the municipal network about the importance, the need and the ways to address the respective issues, the GTES offers continuous training in the themes related to sexual and gender diversity. The study identifies that although the GTES has already had more than 20 years of activity, its institutionalization is recent through an Administrative Rule, and the group still faces structural difficulties - lack of specific materials and didactic resources, lack of government support, resistance of schools and teachers to insert pedagogical approaches to sexuality and its diversity within the classroom. Among the barriers faced for the effectiveness of the work guided by the GTES, the strong influence of the prejudice of teachers, who are largely influenced by their religious affiliations, stands out; in this case, the Evangelical religion evidenced that in the sample of 12 teachers, 3 are totally resistant to the theme even though they have had training in the GTES, and among the teachers who show flexibility and interest in discussing and working on the theme, there is a lack of religion and belonging to the Catholic and / or Spiritist religions. The prejudice, heteronormative culture as a standard and the lack of insertion of the themes in the school curriculum show that, in spite of the advances achieved, the GTES still has great challenges in order to promote formations that allow the disruption of teachers with the prejudice rooted in their cultures and religious influences.